2019
DOI: 10.1136/bmjopen-2018-021820
|View full text |Cite
|
Sign up to set email alerts
|

Needs and rights awareness of stroke survivors and caregivers in urban and rural China: a cross-sectional, multiple-centre questionnaire survey

Abstract: ObjectivesStroke survivors require assistance and support in their daily lives. This survey aims to investigate the needs and rights awareness in Chinese stroke survivors and caregivers in rural and urban settings.SettingThis survey was adapted from the one created by the World Stroke Organization. The questionnaire included demands for psychological support, treatment and care, social support and information. From January 2015 to January 2016, the survey was pilot tested with urban and rural-dwelling stroke s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…However, the clinical focus on stroke in China is still primarily on disease management, often neglecting mental health and cognitive function ( 28 ). A multi-center study revealed that 62.7% of stroke survivors necessitated psychological support, and underscored the insufficiency of available psychological support services ( 29 ). Additionally, while health insurance now covers over 95% of Chinese citizens ( 30 ), there is still a lack of resources to address mental health needs, which is attributed to constraints in medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical focus on stroke in China is still primarily on disease management, often neglecting mental health and cognitive function ( 28 ). A multi-center study revealed that 62.7% of stroke survivors necessitated psychological support, and underscored the insufficiency of available psychological support services ( 29 ). Additionally, while health insurance now covers over 95% of Chinese citizens ( 30 ), there is still a lack of resources to address mental health needs, which is attributed to constraints in medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…Pontuações altas nessa dimensão se associam a pontuações altas no bem-estar psicológico e espiritual. Os cuidadores que não recebem informação adequada acerca da gestão da doença não estão preparados para atender seus familiares e portanto sofrerão maior estresse e serão mais afetados pela carga do cuidado, (28,29) o que afeta a qualidade de vida desse grupo. As necessidades de informação influenciam nos processos de aprendizagem para assumir o papel de cuidador e sua evolução ao longo do tempo.…”
Section: Discussionunclassified
“…Meanwhile, the psychosocial domain is the weak link in the comprehensive rehabilitation of stroke patients ( 16 ). A study conducted in China revealed that of the stroke survivors surveyed, 93.5 and 62.7% needed psychological support and social support, respectively ( 17 ). One scholar clearly points out that there is a need to focus on psychological and social factors in the community rehabilitation process in China ( 18 ).…”
Section: Discussionmentioning
confidence: 99%